Kealpaan Anak yang Menimbulkan Kecelakaan Lalu Lintas yang Mengakibatkan Kematian Orang Lain - Hannah Tiara Delia (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe negligence of a person who causes a traffic accident which results in the loss of another person's life can be punished under the provisions of Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation. However, in cases with child offenders, the provisions contained in Law Number 11 of 2012 concerning the Criminal Justice System for Children apply, so that there is a specificity in the imposition of the sentence. This research will discuss about the form of legal responsibility for children who because of their negligence cause traffic accidents that result in the death of others, then also discuss the ratio decidendi of judges in deciding related cases. This research is a doctrinal research using a statute approach, a conceptual approach and a case approach. The results in this study are the form of legal responsibility for children who due to their negligence causing traffic accidents that result in the death of other people, can be in the form of criminal imposition or action. As for judges in deciding cases must be based on the provisions that contained in Law Number 11 of 2012 and prioritize Restorative Justice.Keywords: Traffic Accident; Child Offender; Negligence; Restorative Justice; Diversion.AbstrakKealpaan seseorang yang menimbulkan kecelakaan lalu lintas yang mengakibatkan hilangnya nyawa orang lain dapat dipidana berdasarkan ketentuan Pasal 310 ayat (4) Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan. Namun demikian dalam perkara dengan pelaku Anak berlaku ketentuan yang terdapat dalam Undnag-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak, sehingga terdapat kekhususan dalam penjatuhan pidananya. Penelitian ini akan membahas mengenai bentuk pertanggungjawaban hukum anak yang karena kealpaannya menyebabkan kecelakaan lalu lintas yang mengakibatkan kematian orang lain, kemudian membahas pula mengenai ratio decidendi hakim dalam memutus perkara terkait. Penelitian ini merupakan doctrinal research dengan menggunakan pendekatan perundang-undangan, pendekatan konseptual dan pendekatan kasus. Hasil dalam penelitian ini yaitu bentuk pertanggungjawaban hukum anak yang karena kealpaannya menyebabkan kecelakaan lalu lintas yang mengakibatkan kematian orang lain dapat berupa pengenaan pidana atau tindakan. Adapun hakim dalam memutus perkara harus berlandaskan pada ketentuan Undang-Undang SPPA dan mengutamakan Keadilan Restoratif.Kata Kunci: Kecelakaan Lalu Lintas; Pelaku Anak; Kealpaan; Keadilan Restoratif; Diversi.